Possible Population Growth of Astrospartus mediterraneus (Risso, 1826) (Ophiuroidea, Gorgonocephalidae) in the Mediterranean Sea - Martina Canessa; Federico Betti; Marzia Bo; Francesco Enrichetti; Margherita Toma; Giorgio Bavestrello (Diversity, 2023)
During the last decades, the number of observations of the basket star Astrospartus mediterraneus (Risso, 1826) in the Mediterranean Sea has significantly grown, thanks to SCUBA diver and ROV sightings, citizen reports, as well as particularly large catches by the artisanal fishery. Having been generally considered rare in many areas of the basin, such a long-term increase of records might assign to this basket star the putative role of a winner species in the context of climate changes. In the present study, we combined the overall literature information with the data available for the Ligurian Sea collected during extensive ROV campaigns conducted between 2012 and 2022 at a depth ranging from 20 to 123 m, to better understand the distribution and abundance of this species. The basket star was observed in almost the whole explored bathymetric range living on gorgonians (Eunicella cavolini, E. verrucosa, Paramuricea clavata, and Leptogorgia sarmentosa) and massive sponges (Aplysina cavernicola, Sarcotragus foetidus, Spongia lamella, and Axinella polypoides). In the considered period, the number of recorded specimens did not show a clear trend, but differences emerged over years and months. These variations were strongly correlated with rainfall amounts that, in oligotrophic waters, such as those of the Ligurian Sea, represent an important input of organic matter for these passive filter feeders, especially in the summertime.